2021
DOI: 10.4103/ijo.ijo_3705_20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the parental satisfaction for retinopathy of prematurity screening using binocular indirect ophthalmoscopy versus wide field retinal imaging

Abstract: Purpose: Analysis of the parental satisfaction for retinopathy of prematurity screening using binocular indirect ophthalmoscopy versus wide field retinal imaging. Methods: This was an observational, questionnaire survey-based study. The study cohort comprised of parents/legal guardians of consecutive Asian Indian premature infants enrolled for retinopathy of prematurity screening (for infants less than 2000 gms and/or 34-weeks gestational age) using binocular indirect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Scholars Dhami Abhinav and others found that the noncontact nature of OCT makes it more acceptable to patients, especially in minor patients, and patient satisfaction with OCT is significantly higher than that of routine examination [ 23 ]. However, the sensitivity of OCT alone in detecting high myopia retinopathy is only 80.0%, presenting certain improvement potential.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars Dhami Abhinav and others found that the noncontact nature of OCT makes it more acceptable to patients, especially in minor patients, and patient satisfaction with OCT is significantly higher than that of routine examination [ 23 ]. However, the sensitivity of OCT alone in detecting high myopia retinopathy is only 80.0%, presenting certain improvement potential.…”
Section: Discussionmentioning
confidence: 99%
“…Highresolution images can be obtained by a physician or trained non-medical personnel; a pediatric retina/ROP specialist evaluates them. Images are classified according to stage, extent, zone, and presence or absence of "plus" disease (Figure 1) [26,27]. Also the use of a smartphone may offer an exciting method for quick ROP documentation (and further primary referral).…”
Section: Imaging Systems 351 Fundus Imagingmentioning
confidence: 99%
“…Despite the procedures being performed by a “vitreoretinal surgeon” who admittedly was in the “learning curve” of using the camera and that too “in front of the parents,” the parents preferred WFI over BIO. [ 1 ] This manuscript highlights yet another advantage of image-based ROP screening over conventional BIO.…”
mentioning
confidence: 99%